(3GdLOjO aj GdeMGSHI GdVQjHjIs - (3YaGfI(B, (3YOjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2004)
(3eONd dOQGSI VQjHI GdONd(B: (3VQjHI GdONd aj GdCQOf, GdJYQja HbGfhf VQjHI GdONd aj GdCQOf, JbOjQ VQjHI GdehXajf hGdeSJNOejf, JbOjQ GdVQjHI GdebWhYI, GdJbOjQ GdVQjHj Ydi Gdecdajf aj eOjQjGJ VQjHI GdONd aj MGdI YOe eSc MSGHGJ CUhdjI, GdJbOjQ GdVQjHj Ydi Gdecdajf aj eOjQjGJ VQjHI GdONd aj MGdI eSc MSGHGJ CUhdjI, GdJbOjQ GdVQjHj Ydi eOjQjI GdTQcGJ GdeSGgeI, ehGVjY eJbOeI aj GdeMGSHI GdVQjHjI(B.s
(3GdeQGLY U(B.495s
Keywords: (3GdVQGFHs; (3GdeMGSHI GdVQjHjIs